End-of-life vehicle management: a comprehensive review - Karagoz, Selman; Aydin, Nezir; Simic, Vladimir (SPRINGER, 2020)
Waste management is gaining very high importance in recent years. As automotive is one of the most critical sectors worldwide, which is rapidly increasing, the management of end-of-life vehicles (ELVs) gains importance day by day. Due to legislation and new regulations, actors like users, producers, and treatment facilities are being conferred new responsibilities in the ELV management process. Besides, the ELV management is of vital importance for environment conservation, circular economy and sustainable development. All of these reasons are making the ELV management such a crucial issue to study. Today, the ELV management is a well-positioned and emergent research area. However, the available review papers are focused only on a small area of the ELV management, such as reverse logistics, recovery infrastructure, disassemblability, etc. Besides, a review of state-of-the-art mathematical models for the ELV management is still missing. This paper aims to provide an extensive content analysis overview of studies on the ELV management. A total of 232 studies published in the period 2000-2019 are collected, categorized, reviewed and analyzed. A critical review of the published literature is provided. Gaps in the literature are identified to clarify and suggest future research directions. This review can provide a source of references, valuable insights, and opportunities for researchers interested in the ELV management and inspire their additional attention.
Keywords: End-of-life vehicle; Management; Waste; Recycling; Review; AUTOMOBILE SHREDDER RESIDUES; LINEAR-PROGRAMMING MODEL; LOOP SUPPLY CHAIN; LOCATION-ALLOCATION PROBLEM; CYCLE ASSESSMENT; REVERSE LOGISTICS; AUTOMOTIVE INDUSTRY; RECYCLING SYSTEM; DECISION-MAKING; PASSENGER CARS; Environmental Sciences & Ecology